Analisis Pengaruh ROE, PER, EPS, DER Dan PBV Terhadap Return Saham (Indeks LQ45 BEI 2021-2024) - Ihsan, Endrian; Dwi Nugroho , Arief Himmawan (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
ABSTRACT A number of factors, including the company's basic circumstances and market perceptions of investment risk, have a substantial impact on the stock returns that investors earn from capital market investing operations. The purpose of this study is to investigate how the stock returns of LQ45 index businesses listed on the Indonesia Stock Exchange between 2021 and 2024 are impacted by Return on Equity (ROE), Earnings Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Price to Book Value (PBV). There are 108 samples in the study sample that fit the requirements. Multiple linear regression analysis is the data analysis technique employed. According to the research findings, ROE, PER, DER, and PBV have no discernible impact on stock returns, while EPS has a considerable one.